Hormone-Producing Ability of Testicular Interstitial Cells and Organotypic Testicular Culture of Newborn Piglets After Cryopreservation - Pakhomov, A. V.; Bozhok, G. A.; Legach, E. I.; Bondarenko, T. P. (Problems of Cryobiology and Cryomedicine, 2007)
The ability of newborn piglet testicular interstitial cells and organotypic testicular culture to basal and stimulated testosterone production after cryopreservation has been comparatively analysed. There were shown different ways of steroidogenesis activation after equilibration with cryoprotectant and freeze-thawing procedures.